Composite materials and their damage detection using AI techniques for aerospace application: A brief review. (2021) - Das, Monalisa; Sahu, Sasmita; Parhi, D.R.
Abstract: Materials for different structural and machine elements have gained importance from last two decades. With the hi-tech age, scientists are interested in specialised materials with specific properties. So, in last two decades utilization of composite materials has been rapidly increasing in order to fulfil the requirements of Aeronautical, space and nuclear sectors. Fibre reinforced polymer matrix composites gained significance role by replacing the conventional metallic materials in many aspects though they are having high performance characteristics, high specific stiffness and strength, weight saving ability, tailored into any critical structural shape, resistance to fracture and fatigue, damage tolerance and greater resistance to oxidation. Present study provides a brief review on various composites used in aeronautical engineering with focus on specific characteristics and features of composites required for aerospace structural members and their benefits.